2009
DOI: 10.1038/jhg.2009.124
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of a subset of ribosomal protein genes in cell lines derived from human nasopharyngeal epithelium

Abstract: Extraribosomal functions of human ribosomal proteins (RPs) include the regulation of cellular growth and differentiation, and are inferred from studies that linked congenital disorders and cancer to the deregulated expression of RP genes. We have previously shown the upregulation and downregulation of RP genes in tumors of colorectal and nasopharyngeal carcinomas (NPCs), respectively. Herein, we show that a subset of RP genes for the large ribosomal subunit is differentially expressed among cell lines derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 10 publications
2
16
1
Order By: Relevance
“…While this expression phenomenon reinforced the fact that they are likely candidates of NPC-associated RP factors, their expression behaviors contradict our previous report [7] of downregulation in NPC cells. Such discrepancy is difficult to explain, but, needless to say, our current findings are more definitive due to the greater accuracy of quantitative RT-PCR over semiquantitative strategy.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…While this expression phenomenon reinforced the fact that they are likely candidates of NPC-associated RP factors, their expression behaviors contradict our previous report [7] of downregulation in NPC cells. Such discrepancy is difficult to explain, but, needless to say, our current findings are more definitive due to the greater accuracy of quantitative RT-PCR over semiquantitative strategy.…”
Section: Discussioncontrasting
confidence: 51%
“…Early evidence of RP genes involvement in NPC was limited to RPeS26 (RPS26), RPeS27 (RPS27), RPuS19 (RPS15), RPeL27 (RPL27), RPeL43 (RPL37a), and RPeL41 (RPL41) [5–7]. Albeit providing information on NPC-associated RP genes, these preliminary findings are largely speculative due to analysis that are semiquantitative in nature and/or confined to assessment at transcript level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rp have been found overexpressed in cancer, for example rpL19, rpL7a, rpL37 in prostate cancer24 rpL15 and rpL19 in gastric cancer2526. The expression of other rp was found reduced as rpL27, rpL37, rpL41 in a subset of cell lines derived from nasopharyngeal carcinomas27. Changes in the expression levels of rps have been used as prognostic or predictive values to distinguish between normal and cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that the ribosomal protein large subunit (RPL) genes of RPL27, RPL37a and RPL41 are significantly downregulated in cell lines derived from nasopharyngeal carcinoma (NPC) compared to a derivative from normal nasopharyngeal epithelium [6], [7]. However, limited studies on protein-protein interaction activities have made the understanding of their extraribosomal roles difficult.…”
mentioning
confidence: 99%